The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018 - Xiang Zeng; Zhongmin Hu; Anping Chen; Wenping Yuan; Guolong Hou; Daorui Han; Minqi Liang; Kai Di; Ruochen Cao; Dengnan Luo (Global Change Biology, 2022)
The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt , and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt , while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change.

Large soil organic carbon increase due to improved agronomic management in the North China Plain from 1980s to 2010s - Daorui Han; Martin Wiesmeier; Richard T. Conant; Anna Kühnel; Zhigang Sun; Ingrid Kögel‐Knabner; Ruixing Hou; Peifei Cong; Rubiao Liang; Zhu Ouyang (Global Change Biology, 2018)
Agricultural soils are widely recognized to be capable of carbon sequestration that contributes to mitigating CO 2 emissions. To better understand soil organic carbon ( SOC ) stock dynamics and its driving and controlling factors corresponding with a period of rapid agronomic evolution from the 1980s to the 2010s in the North China Plain ( NCP ), we collected data from two region‐wide soil sampling campaigns (in the 1980s and 2010s) and conducted an analysis of the controlling factors using the random forest model. Between the 1980s and 2010s, environmental (i.e. soil salinity/fertility) and societal (i.e. policy/techniques) factors both contributed to adoption of new management practices (i.e. chemical fertilizer application/mechanization). Results of our work indicate that SOC stocks in the NCP croplands increased significantly, which also closely related to soil total nitrogen changes. Samples collected near the surface (0–20 cm) and deeper (20–40 cm) both increased by an average of 9.4 and 5.1 Mg C ha −1 , respectively, which are equivalent to increases of 73% and 56% compared with initial SOC stocks in the 1980s. The annual carbon sequestration amount in surface soils reached 10.9 Tg C year −1 , which contributed an estimated 43% of total carbon sequestration in all of China's cropland on just 27% of its area. Successful desalinization and the subsequent increases in carbon (C) inputs, induced by agricultural projects and policies intended to support crop production (i.e. reconstruction of low yield farmland, and agricultural subsidies), combined with improved cultivation practices (i.e. fertilization and straw return) since the early 1980s were the main drivers for the SOC stock increase. This study suggests that rehabilitation of NCP soils to reduce salinity and increase crop yields have also served as a pathway for substantial soil C sequestration.

Changes and controlling factors of cropland soil organic carbon in North China Plain over a 30-year period - Daorui Han; Zhigang Sun; Fadong Li; Ruixing Hou; Jing Li; Zhu Ouyang; Binbin Li; Changwei Cao (Plant and Soil, 2016)